ANALISIS NATRIUM DODESILBENZENA SULFONAT DALAM IKAN LELE SECARA MASERASI DAN SPEKTROFOTOMETRI UV-VIS MENGGUNAKAN METILEN BIRU - Kahar Muzakar; Adhitasari Suratman; Roto Roto (Tanjungpura University, 2020)
Method validation of sodium dodecylbenzene sulfonate (SDBS) analysis in catfish by maceration and UV-Vis spectrophotometry using methylene blue active substances (MBAS) method was performed. The first stage of this research was method validation comprising correlation coefficient, sensitivity, Limit of Detection (LOD), Limit of Quantitation (LOQ), precision, and accuracy. The extraction of SDBS by maceration with methanol for 16 h and analysis by UV-Vis spectrophotometry using MBAS were performed. Then, this method was applied to analyze SDBS in catfish. The results of validation of SDBS analysis in cultivated catfish give correlation coefficient 0.9944, sensitivity 10.57 × 104 L mol-1 cm-1, LOD 0.01776 mg/L, LOQ 0.05922 mg/L, precision 0.1351-1.300 %, and accuracy 87.64-90.01 %, respectively. The SDBS concentrations in fish increase with the increase in the SDBS concentration in cultivating water. Bioconcentration Factor (BCF) values were inversely proportional to the concentration of SDBS in the cultivating water. The concentrations of SDBS on catfish, tilapia, and carp in traditional markets were 5.719-8.162; 5.180-6.548; and 2.973-5.874 mg/kg, respectively. In general, analysis method of SDBS in catfish by maceration and UV-Vis spectrophotometry with MBAS show a good result and can be used as a routine analysis in fish.